The Value of Panoramic Radiograph as a Screening Tool Prior to Complete Denture Construction: A Restrospective Study - Ahmad, Rohana; Affandi, Nurul Farahida; Ayub, Nur Aliya Filza Mohd; Mustafa, Nur Atikah; Yusof, Mohd Yusmiaidil Putera Mohd; Dom, Tuti Ningseh Mohd (Journal of Dentistry Indonesia, 2019)
Objective: The aim of this study was to determine the frequency of detecting abnormal radiographic findings from a diagnostic panoramic radiograph of edentulous patients prior to complete denture constructions. Methods: We reviewed the dental records and panoramic radiographs of 194 edentulous patients receiving complete denture treatment over a 5-year period. We identified cases with recorded abnormal radiographic findings which did or did not require intervention prior to complete denture fabrication. Results: Radiographic abnormalities were detected in 24 of 194 cases (13%), of which 11 cases (6%) required intervention prior to denture construction. Of those 11 cases, 7 had a retained root which required extraction and 4 had irregular ridges which required alveoloplasty. The remaining 170 patients (87%) had no abnormal findings detected on their panoramic radiographs. Conclusion: Abnormal radiographic findings that affect denture construction were only found in 6% of patients, similar to the previous reports. Therefore, taking panoramic radiographs prior to complete denture construction offers insignificant clinical value and should, thus, be discontinued as a screening tool.